Structural Insight into Inhibition of CsrA-RNA Interaction Revealed by Docking, Molecular Dynamics and Free Energy Calculations. Issue 1 (December 2017) - Ren, Xiaodong; Zeng, Rui; Tortorella, Micky; Wang, Jinming; Wang, Changwei
Abstract The carbon storage regulator A (CsrA) and its homologs play an important role in coordinating the expression of bacterial virulence factors required for successful host infection. In addition, bacterial pathogens with deficiency of CsrA are typically attenuated for virulence. In 2016, the first series of small-molecule inhibitors of CsrA-RNA interaction were identified, which were found to achieve the CsrA-RNA inhibition by binding to the CsrA, without interfering with the RNA. However, the binding mechanism of these inhibitors of CsrA is not known. Herein, we applied molecular docking, molecular dynamics and binding free energy calculations to investigate the binding mode of inhibitors to CsrA. We found that the G11 (RNA)-binding site is the most important binding site for CsrA inhibitors. An inhibitor with the proper size range can bind to that site and form a stable complex. We also found that inhibitors with larger size ranges bind to the entire CsrA-RNA interface, but have loose binding. However, this loose binding still resulted in inhibitory activity. The calculated binding free energy from MM/GBSA has a good correlation with the derived experimental binding energy, which might be used as a tool to further select CsrA inhibitors after a first-round of high-throughput virtual screening.